VD_FINDINFO AI 34/12 - 329/2012 vom 27. September 2012 - VD Tribunal cantonal (2012)
RENTE D'INVALIDITÉ, EXPERTISE PLURIDISCIPLINAIRE | 57 al. 1 let. f LAI, 43 al. 1 LPGA, 43 al. 2 LPGA, 44 LPGA, 60 al. 1 LPGA, 61 let. b LPGA, 69 RAI, 82 LPA-VD, 98 let. b LPA-VD